Transition of Draupadi from Damsel in Distress to Deity of Retribution in Kavita Kane‟s Karna’s Wife - Bisht, Yashika (International Journal of Psychosocial Rehabilitation, 2020)
As per Kavita Kane, “Draupadi remains one of the most unloved woman in Mahabharata, who is more associated with hate and revenge and fury than the softer emotions which she was not allowed to indulge in(Kalidoss).” The character of Draupadi is that of an invulnerable woman who encountered all the odds and came out as a self-willed and boisterous woman giving an execrable time to her antagonists. She is married to five Pandavas who are considered to be the mightiest but still she suffers ignominy at the hands of the Kauravas in front of her husbands who are the ones responsible for putting her at stake. It would be engrossing to see how Draupadi suffers at the hands of the men and how she retaliates to her defamation and what does it lead to? Does she sit in a corner of her room for the rest of her life, heartbroken over what her husbands have done to her or chooses to give a resounding comeback?